Factors Influencing Communication Satisfaction Among E-Mail Users in Selected Private Organisations in Indonesia - H. Suyadi, Tuti Iriani (2006)
The most popular method of computer mediated communication in organisation is email. A large number of the uses of e-mail in an organisational setting could in fact be classified into the dimension of task related use and social use. Therefore, it is the aim of this study to determine the influence of e-mail use factors (experience, task, and social related e-mail usage and user characteristics) on communication satisfaction of e-mail users. The study investigated the difference between user characteristics and communication satisfaction; relationship between e-mail usage factors and communication satisfaction; and predictors of e-mail usage factors towards communication satisfaction among e-mail users. The present study used survey design in order to achieve the objectives of the study. Purposive sampling was used to select a total of 305 employees of four selected private companies. The study used self-administered structured questionnaires as the research instrument. Statistical analyses used in this study were the Chi-Square, Pearson Product Moment Correlation and Stepwise Multiple Regression. This study discovered that the employees experienced moderate to high level of communication satisfaction while using e-mails to communicate. There were no significant differences on the communication satisfaction between gender, age, educational attainment and position respectively. Frequency of using e-mail icon influenced communication satisfaction of e-mail users, while number of years of using e-mail did not influence communication satisfaction. Task related e-mail usage (exchange information and decision making) and social related e-mail usage (interpersonal need and relationship development) had significant positive relationship with communication satisfaction. Task related e-mail usage and social related e-mail usage was a significant predictor of communication satisfaction. However, relationship development is a major determinant influencing communication satisfaction among e-mail users. This study recommended that task and social related e-mail usage should be considered as interdependent dimensions bye-mail users as both would contribute towards communication satisfaction that have potential impact on the organisations.